Global Crisis in the Outbreak of Emerging Infectious Diseases: The Role of the World Health Organization, a Situation in Thailand and a New Normal - Sangwongdee, Punyaphat (Journal of Social Synergy, 2020)
Emerging Infectious Diseases are an epidemic that transmit from animals to humans and from person to person including those new infectious diseases, re-emerging infectious diseases, new geographical areas, mutated diseases. These emerging diseases are considered a global health crisis and they tend to increase in number with increasing in their severity. Therefore, it is necessary to have an international social welfare organization which includes the world health organization acts as the main body of health and public health in the world to take a lead role in operations especially in an international public health emergency that every countries globally needs help, support, advice and coordination to stop the spread of emerging infectious diseases and reduce the losses that may occur to a minimum. The World Health Organization is projecting the operations for international social welfare care. In Thailand, Thai government, as a provider of a country social welfare to its people in emergencies, has put efforts in implementing a disease control in line with the International Health Regulation by healing the people who are suffering through Social insurance, Social assistance and Social service which involved private sectors, public sectors, and the community. This involvement reflects the social capital of Thailand. The emerging outbreak of this emerging infectious diseases will be with the world shortly. Because ultimately humans have to find a way to solve the problem; however, what is changing is behavioral patterns that subsequently become a “New Normal” lifestyle that we, humans, are more rely on virtual technology.